Breeding Biology of the Fiscal Shrike, Lanius collaris (Laniidae), in a Peri-Urban Environment in Roma (Lesotho) - Kopij, G. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
An urbanized population of the Fiscal Shrike was studied in a